TROMBEKTOMI MEKANIS DAN TROMBOLISIS INTRAARTERI PADA STROKE ISKEMIK: FOKUS PADA LUARAN KLINIS - Listyawan, Rakhian; Setyawan, Tommy Rachmat (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Mechanical thrombectomy has become the standard recommended therapy for acute ischemic stroke due to large vessel occlusion. A series of fundamental clinical trials have demonstrated the superiority of mechanical thrombectomy in achieving functional independence (modified Rankin Scale [mRS] score 0-2) at 90 days compared to medical therapy alone. The therapeutic window for mechanical thrombectomy has even been extended to 24 hours for selected patients based on perfusion imaging. Meanwhile, the role of intraarterial thrombolysis has evolved from primary therapy to an adjunctive or rescue strategy, used in cases of incomplete recanalization or distal embolism after mechanical thrombectomy. Both treatment modalities continue to evolve to improve clinical outcomes in patients. Keywords: Ischemic stroke, mechanical thrombectomy, intraarterial thrombolysis, large vessel occlusion, clinical outcome.